Interconnected Disaster Management - Bridging the Physical and Digital Divide. Issue 3 (3rd July 2021) - Brown, Heather
ABSTRACT: When a disaster strikes, major damage can occur to physical and digital collections. However a major research project, undertaken in the context of Australian national state and territory (NSLA) libraries, has uncovered that the approaches to the disaster management of physical and digital collections are largely divided and uncoordinated. The outcomes of the research project have demonstrated the benefits and feasibility of integrating disaster management across all collection formats – physical and digital, while also noting barriers and areas of disconnect. A practical application of the research has been the updating of the ALIA disaster management resources, as a 'one stop shop' integrated approach to managing disasters across all collection formats. Overall, at a time of elevated risk of disasters due to climate change, this research provides an important contribution to the field of disaster management with an integrated perspective that has potential application across the wider GLAM sector within Australia, and internationally, with organisations such as Blue Shield International.